2015
DOI: 10.1039/c5ra03069b
|View full text |Cite
|
Sign up to set email alerts
|

Revealing a room temperature ferromagnetism in cadmium oxide nanoparticles: an experimental and first-principles study

Abstract: CdO nanoparticles obtained from a thermal decomposition, show a room temperature ferromagnetism due to the cadmium and oxygen defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…This is an evidence of a weak ferromagnetic order despite the diamagnetic nature of the CdO itself. This agrees well with the reported ferromagnetic behavior of CdO (Bououdina et al 2015). The difference here is annealing atmosphere where our system is annealed in air.…”
Section: Resultssupporting
confidence: 81%
“…This is an evidence of a weak ferromagnetic order despite the diamagnetic nature of the CdO itself. This agrees well with the reported ferromagnetic behavior of CdO (Bououdina et al 2015). The difference here is annealing atmosphere where our system is annealed in air.…”
Section: Resultssupporting
confidence: 81%
“…It is possible in the NPs, above a percolation threshold, strong mutual interactions of magnetic moments, associated with the defected states, really take place and the long-range ferromagnetic order may be established. The most likely, these interacting vacancies contribute to the net RTFM magnetization of our NPs [19,103].…”
Section: S O Kllmentioning
confidence: 98%
“…It is known that undoped, bulk and stoichiometric CdO powder has diamagnetic (DM) properties at RT [24]. However, it was observed that structural point defects like vacancies could create in CdO a very weak FM component superimposed on the main DM characteristics (i.e., DM+FM) [25]. However, for practical applications in DMS, it is necessary to create stable and considerable FM properties from spin-spin (S.S) exchange interaction between dopant ions.…”
Section: Magnetic Propertiesmentioning
confidence: 99%